1987
DOI: 10.1515/jnet.1987.12.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Potential Measurements for Selectivity Determinations of Polycarbonate Membranes Bounded by LiCl Solutions

Abstract: Membrane system potentials and apparent transport numbers of the cation are reported for six polycarbonate membranes bounded by LiCI aqueous solutions using chloride-selective electrodes. The membranes have pore diameters ranging from 5.0-0.03 μιη. The concentrations of the bounding solutions vary from 2.10" 4 -10" 1 mol/dm 3 and the measurements have been carried out at temperatures of 10, 30, 40 and 50 °C.Our results show that polycarbonate membranes are cationic selective when the concentrations of the boun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…A previous study [3] on the ionic selectivity has shown that for the Ν 5 membrane D p = D d at every temperature and concentration studied. So in order to calculate δ from Eq.…”
Section: Thickness Of Diffusion Layersmentioning
confidence: 78%
See 2 more Smart Citations
“…A previous study [3] on the ionic selectivity has shown that for the Ν 5 membrane D p = D d at every temperature and concentration studied. So in order to calculate δ from Eq.…”
Section: Thickness Of Diffusion Layersmentioning
confidence: 78%
“…a) The ionic selectivities of these membranes have been studied for the same temperatures and concentrations [3]. From that we obtained that these quantities approach zero for membranes with great pore diameters and for high concentrations, which means that pore diffusion approaches free diffusion (D p ^ D d ).…”
Section: Salt Permeabilitymentioning
confidence: 90%
See 1 more Smart Citation
“…The potential arising across the membrane system was studied by constructing a cell of the type: emf, Ec, of this cell was measured by using the two-compartment cell shown in a previous paper (2). This method allowed keeping the concentrations Nl and N2 constant because both solutions have agitation and renovation systems available.…”
Section: Methodsmentioning
confidence: 99%
“…and ionic selectivity [3] etc. The Nuclepore membranes, made of polycarbonate, were commonly used in these researches.…”
Section: Introductionmentioning
confidence: 99%